GPR15LG binds CXCR4 and synergistically modulates CXCL12-induced cell signaling and migration - Dan Pascal Jean Albers; Sofya Novikova; Julio Vieyto-Nuñez; Yasser Almeida-Hernández; Chiara Pastorio; Florian Klassen; Dana Weiss; Pascal von Maltitz; Janeni Jaikishan; Moumita Datta; Hassan Jumaa; Billy Michael Chelliah Jebaraj; et al. (Cell Communication and Signaling)
Abstract Background GPR15LG, a chemokine-like ligand for the G-protein coupled receptor 15 (GPR15), is abundantly expressed in the gastrointestinal mucosa and inflamed skin. Emerging evidence suggests its involvement in inflammatory disorders and cancers. C-X-C chemokine receptor type 4 (CXCR4) plays a critical role in immune cell trafficking and cancer metastasis. Recent evidence suggests a connection between GPR15LG and CXCR4 signaling, which has not been investigated so far. Methods We investigated the effects of GPR15LG on CXCR4 signaling and downstream functions. Binding assays and computational modeling were performed to assess the interaction between GPR15LG and CXCR4. Functional assays, including wound healing and cell migration assays, were conducted across various cell types, including CD4⁺ T cells and cancer cells, to evaluate the impact of GPR15LG on CXCL12-mediated CXCR4 signaling. Results The results demonstrate that GPR15LG binds to the orthosteric site of CXCR4, modulating downstream signaling in a context-dependent manner. Specifically, GPR15LG enhances CXCL12-mediated CXCR4 signaling synergistically, promoting wound healing and cell migration across various cell types, including CD4 + T cells and cancer cells. Conclusions These findings underscore the role of GPR15LG in inflammation and metastasis, offering potential therapeutic avenues for CXCR4-mediated diseases.